SINERGITAS STAKEHOLDERS DALAM PEMBANGUNAN RUANG TERBUKA HIJAU (RTH) HOTEL DI KOTA PONTIANAK - Nurianti, Rita; Mardhalena, Azrita; Rahim, Abdul (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2023)
The purpose of this research was to describe and analyze the synergy of stakeholders in the development of Green Open Space (RTH) in Pontianak City. The research problem was that the synergy between stakeholders in the development of green open space hotels had not been going well because the land was narrow and they did not understand about the development of green open spaces. This research used descriptive research type through qualitative approach. The theory used in this research was the theory of Najiyati (2011: 121), namely the concept of synergy which can be built through: communication and coordination. The research results indicated that; (1) communication in building synergy, namely the delivery of messages carried out by communicators to communicators through downward communication and upward communication as well as diagonal communication. The forms of communication used by stakeholders in increasing the development of green open spaces were still not achieved by 30% of the area, especially the construction of green open space hotels which were still below 10% in Pontianak City. (2) Coordination between the Pontianak City Public Works and Spatial Planning Office and business owners was still not good in the development of green open spaces in Pontianak city. Keywords: Synergy, Stakeholders, Green Open Space Development